1973
DOI: 10.1021/ja00790a013
|View full text |Cite
|
Sign up to set email alerts
|

Composition of complex aluminum hydrides and borohydrides, as inferred from conductance, molecular association, and spectroscopic studies

Abstract: The equivalent conductance of THF solutions of LiAlH4, NaAlH4, Bu4NA1H4, and LiBH4 were obtained over a wide concentration range, i.e., 0.5 to 1 X 10~7 M. The data are consistent with the presence of free ions and ion pairs in dilute solution and the formation of triple ions as the concentration is increased. The application of the Fuoss treatment to the data, where only free ions and ion pairs are encountered, permits the evaluation of the infinite dilution equivalent conductance ( 0) and the ion-pair dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 1 publication
7
51
0
Order By: Relevance
“…1. Our results are in good agreement with those reported by Ashby et al [4] and Alpatova et al [6]. Molar conductivity of LiAlH 4 2THF solution shows a minimum at around 0.02 M and a maximum at around 1.0 M. In case of NaAlH 4 2THF solution the molar conductivity shows a maximum similar to the case of LiAlH 4 although the minimum is not clear.…”
Section: Nature Of Solutionssupporting
confidence: 92%
See 2 more Smart Citations
“…1. Our results are in good agreement with those reported by Ashby et al [4] and Alpatova et al [6]. Molar conductivity of LiAlH 4 2THF solution shows a minimum at around 0.02 M and a maximum at around 1.0 M. In case of NaAlH 4 2THF solution the molar conductivity shows a maximum similar to the case of LiAlH 4 although the minimum is not clear.…”
Section: Nature Of Solutionssupporting
confidence: 92%
“…Molar conductivity of LiAlH 4 2THF solution shows a minimum at around 0.02 M and a maximum at around 1.0 M. In case of NaAlH 4 2THF solution the molar conductivity shows a maximum similar to the case of LiAlH 4 although the minimum is not clear. As mentioned in Section 1, Ashby et al [4] have provided a detailed information concerning the present species of LiAlH 4 2THF and NaAlH 4 2THF solutions over a wide concentration ð10 À7 20:1 MÞ. They found that at 25 C in dilute solution the predominant species are solvated lithium ion and ½AlH 4 À anion (I); at 0.01 M they are solvent-separated ion pairs (II); and at higher concentrations triple ions (III) are formed by the association of LiAlH 4 through hydrogen bridge…”
Section: Nature Of Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[83]), in LiBH 4 dissolved in organic solvents (stretching vibrations measured by IR spectroscopy, Ref. [84]) and in solid LiBH 4 [62]. An important question related to the effect of additives is wether the additives interact with the hydrides.…”
Section: Sorption Mechanism Of Complex Hydrides Probed By Vibrationalmentioning
confidence: 99%
“…This width is about four times as large as for monoglyme. Since X H broad band decoupling has no influence on the 7 Li line width it seems that the interaction of the Li-cations and AIH4 anions in the ion pair and triple ions present in these solutions [13] is less efficient in these solvents than in the diglyme allowing a more rapid quadrupol relaxation.…”
Section: Discussionmentioning
confidence: 98%